Surface modified cellulose obtained by acetylation without solvents of bleached and unbleached kraft pulps - Olaru, N.; Olaru, L.; Vasile, C.; Ander, P. (Polimery, 2011)
Heterogeneous acetylation to a low extent of bleached and unbleached commercial kraft pulps was performed with acetic anhydride without solvents and in the presence of sulfuric acid catalyst. The process was conducted in an effort to change the polarity of studied kraft pulps and to improve their compatibility with synthetic polymers without changing their fibrous structure. It was observed that the fiber morphology does not change up to a reaction time of 3 h for both investigated materials. The hydrophilic character of the bleached pulp was decreased by acetylation to a low extent, while the unbleached material showed an initial increase of water retention capacity. At higher degrees of modification, both pulps exhibited similar hydrophilic properties. For both materials, an initial slightly increased susceptibility to enzymatic attack with cellulase from Trichoderma reesei was observed, however the acetylated bleached cellulose fibers were more susceptible to enzymatic attack than those of the unbleached material.